ANALYSIS OF CALLIGRAPHY EXTRACURRICULAR ACTIVITIES IN ISLAMIC EDUCATIONAL INSTITUTIONS - Uswatun Hasanah; Laila Rahimah Harahap (Yayasan Haiah Nusratul Islam, 2024)
Extracurricular activities are activities outside of learning hours to hone students' interests, talents and creativity. Creativity is very important in learning, especially in the development of writing Qur'anic verses through calligraphy. Calligraphy Art Extracurricular Activities are a series of teaching and learning activities programs that focus on training and developing calligraphy art. This research uses a qualitative approach, which describes and describes the analysis of calligraphy extracurricular activities in Islamic educational institutions. The data collection technique used in this research is a literature study (Library Research) where literature study is an activity of collecting materials related to research originating from books, scientific journals, literature and other publications that deserve to be used as sources for research that the author will examine, by describing and describing the data is through several opinions of experts. The purpose of this writing is to find out calligraphy extracurricular learning in Islamic educational institutions. And the results of this study resulted in the conclusion that calligraphy extracurricular activities can help improve the ability to develop students.